UPAYA MENURUNKAN TINGKAT KEMISKINAN MELALUI PENINGKATAN KAPASITAS KELOMPOK MASYARAKAT DI KABUPATEN LOMBOK BARAT PROPINSI NUSA TENGGARA BARAT - IDA BAGUS EKA ARTIKA; I WAYAN KEMBARYANA; IDA AYU KETUT MARINI; IDA AYU NOPIARI (GANEC SWARA, 2020)
The poverty reduction strategy is a priority strategy for every local government in Indonesia today with the aim of accelerating poverty alleviation towards a prosperous society. West Nusa Tenggara Province isone of the provinces whose poverty rates are still above the national average, so that various efforts to accelerate poverty alleviation are needed in order to catch up with other regions. This research is conducted on 3 community groups, namely farmers' community groups, fishermen community groups, and crafters community groups in 3 different villages in West Lombok, by conducting a SWOT analysis in order to find the right strategy to accelerate poverty alleviation, especially in the district of West Lombok.The results of the study found that strategies are needed to overcome the weaknesses that exist in community groups, to get opportunities for community empowerment that exists. Programs that need to be carried out are group capacity building programs through mentoring to get empowerment programs by the government, group capacity building programs to gain banking access to increase group venture capital,and community group institutional strengthening programs by making the community groups as cooperatives with legal entities to facilitate the government in providing guidance and distribution of productive revolvingfunds to members